The anti-candidal activity of Pelargonium graveolens essential oils against clinical isolates of Candida albicans - Mohaddese Mahboubi* (Infectio)
Abstract Objectives: Candida albicans as important opportunistic dimorphic fungi can cause the life threatening infections in humans. In this study, we evaluated the anticandidal activities of six samples of Pelargonium graveolens essential oils against 31 clinical isolates of C.albicans. Materials and methods: The anti-candidal activity was performed by disc diffusion and micro-broth dilution assays. The chemical compositions of essential oils were analyzed by Gas Chromatography (GC) apparatus. Results: P. graveolens essential oil samples with citronellol (7.7-43.7%) and geraniol (19.3-48.5%) showed the same anti-candidal activity in two different methods. There is no significant difference between the inhibition zone diameters (19.3-24.1 mm), and the MIC and MFC values (1.06-1.48 and 1.5-1.72 µl/ml) of essential oil samples with different percent of citronellol and geraniol. Conclusion: Therefore, P.graveolens essential oils can be used as anti-candidal agent for further studies.